Högskolestuderandes internationella rörlighet mellan Sverige och Östeuropa - Chefer, Anastasia (2013)
This study is part of the project "Globalized eduscapes: students, learning and mobility in knowledge society" with the aim to study student mobility between Sweden and Eastern Europe. The focus of the study is directed to incoming students, consisting of two groups, and partly by exchange students par-ticipating in exchange programs at universities in Luleå and Umeå, and of students who organize their studies in Sweden on their own, so-called "free-movers" as master students and graduate students. The paper defines to incoming students from Russia, Ukraine and Poland. The purpose of this paper is to study the mobility of students coming from Eastern Europe to Sweden aimed at Luleå University of Technology and Umeå University. The focus of the purpose is mostly in the background of stu-dents on the main question which countries and areas they come from and the reason why they chose to study in Sweden. Empirical approaches have been made through interviews with the selected re-spondents and supplemented by statistical evidence.The theoretical framework addressed from globalization theories comes from the article Eduscapes and interference by Ulf Mellströms (2012), Social change and international relations from Giddens (2003) and Petter Scott (1998) and Bauman's (2001) theory of education under modernity and indi-vidualization, freedom and security.Students who come to Sweden for training purposes given that opportunity by the universities in their home country that has an agreement with Swedish universities. Most students come from Arkhan-gelsk, Yakutsk and Murmansk, of the incoming students is largest number of women who comes to Sweden. Results of the interviews shows that universities in Eastern Europe have deficiencies in the educational system, which affects the quality of education and therefore seek out students to study abroad. These students basically have a strong educational traditions in the family that they follow in the tracks of their parents. Many of these students seeking further on to higher ...